The City Under COVID‐19: Podcasting As Digital Methodology. (9th June 2020) - Rogers, Dallas; Herbert, Miles; Whitzman, Carolyn; McCann, Eugene; Maginn, Paul J.; Watts, Beth; Alam, Ashraful; Pill, Madeleine; Keil, Roger; Dreher, Tanja; Novacevski, Matt; Byrne, Jason; et al.
Abstract: This critical commentary reflects on a rapidly mobilised international podcast project, in which 25 urban scholars from around the world provided audio recordings about their cities during COVID‐19. New digital tools are increasing the speeds, formats and breadth of the research and communication mediums available to researchers. Voice recorders on mobile phones and digital audio editing on laptops allows researchers to collaborate in new ways, and this podcast project pushed at the boundaries of what a research method and community might be. Many of those who provided short audio 'reports from the field' recorded on their mobile phones were struggling to make sense of their experience in their city during COVID‐19. The substantive sections of this commentary discuss the digital methodology opportunities that podcasting affords geographical scholarship. In this case the methodology includes the curated production of the podcast and critical reflection on the podcast process through collaborative writing. Then putting this methodology into action some limited reflections on cities under COVID‐19 lockdown and social distancing initiatives around the world are provided to demonstrate the utility and limitations of this method. Abstract : This commentary discuss the digital methodology opportunities that podcasting affords geographical scholarship. In this case the methodology includes the curated production of the podcast and critical reflection on the podcast process through collaborative writing. Then putting this methodology into action some limited reflections on cities under COVID‐19 lockdown and social distancing initiatives around the world are provided to demonstrate the utility and limitations of this method.